Ciliates along Oxyclines of Permanently Stratified Marine Water Columns - Edgcomb, V P; Pachiadaki, M (Journal of Eukaryotic Microbiology, 2014)
Studies of microbial communities in areas of the world where permanent marine water column oxyclines exist suggest they are "hotspots" of microbial activity, and that these water features and the anoxic waters below them are inhabited by diverse protist taxa, including ciliates. These communities have minimal taxonomic overlap with those in overlying oxic water columns. Some ciliate taxa have been detected in multiple locations where these stable water column oxyclines exist; however, differences in such factors as hydrochemistry in the habitats that have been studied suggest local selection for distinct communities. We compare published data on ciliate communities from studies of deep marine water column oxyclines in Caricao Basin, Venezuela, and the Black Sea, with data from coastal, shallower oxycline waters in Framvaren and Mariager fjords, and from several deep-sea hypersaline anoxic basins in the Eastern Mediterranean Sea. Putative symbioses between Bacteria, Archaea, and ciliates observed along these oxyclines suggests a strategy of cooperative metabolism for survival that includes chemosynthetic autotrophy and exchanges of metabolic intermediates or end products between hosts and their prokaryotic partners.
Keywords: ROV Jason (Remotely Operated Vehicle)